1995
DOI: 10.1254/jjp.69.285
|View full text |Cite
|
Sign up to set email alerts
|

Selective Inhibition of Inducible Nitric Oxide Synthase by Agmatine

Abstract: ABSTRACT-Agmatine was about as potent as aminoguanidine to inhibit the activity of the inducible form of nitric oxide synthase (iNOS) in isolated rat aorta. Like aminoguanidine, agmatine was devoid of significant activity on the constitutive form of NOS. Agmatine inhibited the conversion of [3H]L-arginine in [3H]L-citrulline in partially purified iNOS from macrophages (IC50=262±39.9 pM). Thus, our data suggest that agmatine may act as endogenous inhibitor of iNOS.Keywords: Agmatine, Nitric oxide, Inducible enz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
82
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(88 citation statements)
references
References 15 publications
4
82
0
2
Order By: Relevance
“…In the present study, HI rat pups showed elevations in NO metabolite concentrations in the brain during reperfusion 6 h after hypoxia, and agmatine treatment (100 mg/kg) eliminated this increase in NO metabolites. The results indicate that agmatine suppresses NO production after hypoxia in vivo as is known to occur in vitro (22)(23)(24)(25). Reduction of NO generation may therefore be one mechanism of neuroprotection by agmatine.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In the present study, HI rat pups showed elevations in NO metabolite concentrations in the brain during reperfusion 6 h after hypoxia, and agmatine treatment (100 mg/kg) eliminated this increase in NO metabolites. The results indicate that agmatine suppresses NO production after hypoxia in vivo as is known to occur in vitro (22)(23)(24)(25). Reduction of NO generation may therefore be one mechanism of neuroprotection by agmatine.…”
Section: Discussionmentioning
confidence: 60%
“…Agmatine also inhibits all isoforms of NOS (22)(23)(24)(25), with highest reported activity (Ki ϭ 29 M) as an irreversible inactivator of neuronal NOS (25). Treatments with agmatine are neuroprotective in vitro (21,22), as well as in gerbil ischemic brain injury, adult rat ischemic brain injury (26), and adult rat spinal cord injury (16,27,28). The effects of agmatine in neonatal HI brain injury have not previously been tested, nor has correlation been studied between the neuroprotective properties of agmatine and NO production in the brain.…”
mentioning
confidence: 99%
“…Агматин в організмі діє як нейротрансмітер і нейромодулятор, є ендогенним лігандом для імідазольних рецепторів (І 1 /І 2 ) і, з меншою афінністю, для α 2 -адренорецепторів, N-метил-D-аспартат і серотоніно-вих рецепторів [15]. Як аналог L-аргініну, за рахунок наявності гуанідинової групи, цей поліамін також виконує роль конкурентного інгібітора NO-синтази [8]. Одним із біологічних ефектів агматину в організмі, що реалізуються рецептор-опосередко-ваним шляхом, є здатність впливати на метаболізм глюкози за умов її підвищеної концентрації [12].…”
Section: вступunclassified
“…Agmatine also inhibits all isoforms of NOS (22-25), with highest reported activity (Ki ϭ 29 M) as an irreversible inactivator of neuronal NOS (25). Treatments with agmatine are neuroprotective in vitro (21,22), as well as in gerbil ischemic brain injury, adult rat ischemic brain injury (26), and adult rat spinal cord injury (16,27,28). The effects of agmatine in neonatal HI brain injury have not previously been tested, nor has correlation been studied between the neuroprotective properties of agmatine and NO production in the brain.…”
mentioning
confidence: 99%